Von Preußen lernen? : Die preußische Monarchie im Spiegel französischer Reformdiskurse am Ende des Ancien Régime - Deflers, Isabelle (2021)
With the end of the Seven Years' War, a period of intensive search for reform ideas began in France an attempt to restore France's supremacy in the international state system and save the monarchy from bankruptcy. The particularly lively interest of the French public in Prussia raises the question of the extent to which Frederick II's state, which was regarded as successful, has served as a model in this reform debate. The book shows by which ways, carriers and means the transfer of knowledge from Prussia to France took place at the end of the Ancien Régime and what function the reference to Prussia actually assumed within self-referential French discussions.